Polyketides with IDH1 R132h and PTP1B inhibitory activities from the desert-plant-derived fungus Alternaria sp. HM 134 - Li, Zhuang; Meng, Lu; Ma, Qingyun; Wang, Zhen; Zhao, Youxing; Luo, Duqiang (Frontiers in Microbiology, 2022)
Five new polyketides named alternafurones A (1) and B (2), alternapyrones M-O (3-5), together with fourteen known ones (6-19), were isolated from the desert-plant-derived fungus Alternaria sp. HM 134. The structures of the new compounds were elucidated from spectroscopic data and ECD spectroscopic analyses. Alternafurones A and B represent polyketides with an unprecedented 6/5/6 skeleton core. Compounds 1, 2 and 4 showed definite inhibitory activities against isocitrate dehydrogenase 1 gene (IDH1 R132h) with IC50 values of 29.38, 19.41 and 14.14 μg/mL respectively. Seven compounds (6, 7, 9-12, 14) showed potent protein tyrosine phosphatase 1B (PTP1B) inhibitory activity with IC50 values ranging from 0.97 μg/mL to 89.80 μg/mL.